Interview with Dr Gilbert Wong, Senior Superintendent, Commanding Officer, Police Negotiation Cadre, Hong Kong - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2014)
Editor Nadja Alexander interviews Dr Gilbert Wong (Senior Superintendent, Commanding Officer, Police Negotiation Cadre, Hong Kong) about his work as a crisis negotiator and reflected on lessons for life and business.